An injectable hydrogel based on gradient structure and its preparation method and application
By using gradient structure hydrogel based on copper-sulfur coordination in the treatment of periodontitis, combined with the photothermal properties of polydopamine nanoparticles, the problems of inaccurate drug release and poor mechanical properties in the prior art are solved, and the problem of inaccurate drug release and poor mechanical properties in the prior art is achieved. The effect of intelligent drug release and periodontal tissue regeneration is achieved.
Patent Information
- Application Number
- CN202410911482.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-09
AI Technical Summary
The existing injectable hydrogels are difficult to adapt to the microenvironment of the inflammatory site in the treatment of periodontitis, resulting in inaccurate drug release, poor mechanical properties, and difficult to adapt to the oral environment.
Using a gradient structure hydrogel based on copper-sulfur coordination, a high viscosity organic-inorganic composite network is formed through Cu-N and Cu-S coordination, combining the photothermal properties of polydopamine nanoparticles to realize the intelligent drug. release.
The graded release of drugs is achieved, which can respond to periodontal inflammation microenvironment, clear ROS, and coordinate the treatment of periodontal inflammation, improving the regeneration effect of periodontal tissue.
Smart Images

Figure CN118873486B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical technology, and in particular to an injectable hydrogel based on a gradient structure and a preparation method and application thereof. Background Art
[0002] Periodontitis is a common chronic inflammatory disease characterized by local inflammatory responses and alveolar bone resorption caused by the colonization of pathogenic microorganisms. The pathological microenvironment often contains a large amount of reactive oxygen species (ROS). The increase in ROS levels will not only aggravate local inflammation, but also inhibit the osteogenesis process. Therefore, the coupling process of reducing ROS levels and remodeling osteoblast activity is a prerequisite for promoting in situ periodontal tissue regeneration. Injectable hydrogels are biomaterials with cross-linked three-dimensional polymer network structural characteristics. They have been widely studied because of their structure similar to biological tissues. The special structure, material composition and precise implantation of injectable hydrogels in tissue sites give them unique advantages in drug delivery. They can not only continuously release drugs at the pathological tissue site, but also respond intelligently according to the microenvironmental characteristics of the application site.
[0003] When existing injectable hydrogels are used to treat periodontitis, they form gels in situ by means of temperature changes. Due to the complexity of the microenvironment of the periodontal area, it often takes a long time for the gel to form in situ, and it is difficult for the gel to adapt to the microenvironment of the inflammatory area. The drug-loaded gel cannot accurately control the release of the drug. In addition, the injectable gels currently developed for the treatment of periodontitis have poor mechanical properties and are difficult to adapt to the oral environment due to the weak physical interaction between the polymer chains and the uneven distribution. Therefore, it is very necessary to develop an injectable hydrogel with a gradient structure and loaded with flavonoid drugs that can respond to the periodontal inflammatory microenvironment and intelligently regulate drug release to promote periodontal tissue regeneration. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide an injectable hydrogel based on a gradient structure, a preparation method and an application thereof, wherein the hydrogel is loaded with the flavonoid drug genistein, and is used for the treatment of periodontitis in coordination with the angiogenesis-promoting effect of copper ions. The method is based on the copper-sulfur coordination effect to prepare a hydrogel with a gradient structure, and the gradient structure enables the hydrogel to achieve graded release of drugs when used as a drug carrier, and the ROS responsiveness of the copper-sulfur bond and the photothermal property of polydopamine nanoparticles enable the gel to release drugs intelligently, further improving its practicality for the treatment of periodontitis.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing an injectable hydrogel based on a gradient structure comprises the following steps:
[0007] (1) dissolving polydopamine nanoparticles in a solvent, then adding genistein and stirring to dissolve, and then adding a copper chloride solution and stirring to dissolve to obtain a drug-loaded polydopamine copper chloride solution;
[0008] (2) dissolving the four-arm-polyethylene glycol-thiol group in a solvent to obtain a four-arm-polyethylene glycol-thiol group solution;
[0009] (3) The drug-loaded polydopamine copper chloride solution is mixed with the four-arm-polyethylene glycol-thiol solution to obtain an injectable hydrogel.
[0010] The present invention utilizes the π-π interaction between polydopamine and genistein drugs to achieve efficient loading of hydrophobic drugs, and a high-viscosity organic-inorganic composite network is initially formed between copper ions and polydopamine through Cu-N coordination. Four-arm-polyethylene glycol-thiol is further introduced into the above system, and diffusion-controlled Cu-S coordination is utilized to prepare a polymer hydrogel network with a special gradient structure.
[0011] Preferably, in steps (1) and (2), the solvent is ultrapure water, PBS buffer or physiological saline.
[0012] like Figure 2 As shown, the present invention has found through research that the gelling time of the gel can be effectively regulated by regulating the mass concentration of the copper chloride solution. As the copper ion concentration increases, the gelling time of the gel is continuously reduced. When the prepared copper ion concentration is 0.16wt%, gelling can be achieved within 1 minute. However, when the copper ion concentration is too high, the needle will be blocked, affecting the injection effect, and also increasing cytotoxicity. Therefore, preferably, in step (1), the mass concentration of the copper chloride solution is 0.16-15wt%.
[0013] Preferably, in step (1), the preparation method of polydopamine nanoparticles PDA is as follows: stirring a mixture containing concentrated ammonia water, ethanol and water at room temperature; adding an aqueous solution of dopamine hydrochloride to the mixture and reacting under stirring; separating the polydopamine nanoparticles by centrifugation, washing with water, and drying overnight to obtain the polydopamine nanoparticles. The volume ratio of concentrated ammonia water, ethanol and water is 1-3:20-60:45-135, the concentration of dopamine hydrochloride added is 25-75 mg / mL, the stirring speed is 400-600 rpm, the stirring temperature is 20-30°C, the centrifugal speed is 10000-12000 r / min, and the centrifugal time is 20-30 min.
[0014] Preferably, the mass concentration of the polydopamine nanoparticles in the injectable hydrogel is 4.9-19.6wt‰.
[0015] Preferably, in step (2), the mass concentration of the four-arm-polyethylene glycol-thiol solution is 1 to 25 wt %.
[0016] Preferably, in step (3), the mixing volume ratio of the drug-loaded polydopamine copper chloride solution and the four-arm-polyethylene glycol-thiol solution is 1:1-3:1.
[0017] The present invention also provides an injectable hydrogel based on a gradient structure, which is prepared by the above-mentioned preparation method.
[0018] The present invention also provides the use of the above-mentioned injectable hydrogel based on the gradient structure in the preparation of drugs for treating periodontitis.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The injectable hydrogel provided by the present invention is based on copper-sulfur coordination, and the four-arm star-shaped terminal thiol polyethylene glycol is quickly gelled after being mixed with copper ions. Due to the concentration diffusivity of copper ions during the gelation process, the prepared gel has a gradient structure. The gradient network structure is conducive to the intelligent release of drugs, and the copper-sulfur dynamic coordination bond has ROS responsiveness. When the gel is used in periodontitis sites, it is beneficial to remove ROS in the inflammation site. The polydopamine nanoparticle PDA has good photothermal conversion ability. The gel can intelligently regulate the release of drugs under near-infrared light, and the intelligent release of copper ions and drug genistein can synergistically treat periodontitis. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The scanning electron microscope (left) and transmission electron microscope (right) photos of the polydopamine nanoparticles PDA obtained in Example 1;
[0022] Figure 2 is the effect of copper ion concentration on gelation time;
[0023] Figure 3 The elemental analysis (left) photo and Raman spectrum analysis (right) of the injectable hydrogel obtained in Example 3 are shown in FIG.
[0024] Figure 4 This is a scanning electron microscope image of the injectable hydrogel obtained in Example 3.
[0025] Figure 5 This is the time-scan rheological graph of the injectable hydrogel obtained in Example 3.
[0026] Figure 6 It is a verification picture of the injectability of the injectable hydrogel obtained in Example 3 and the injected letters "Ee".
[0027] Figure 7The injectable hydrogel obtained in Example 3 was illuminated at 808 nm laser 1.1 W / cm 2 Thermal imaging at power density.
[0028] Figure 8 This is a diagram showing the photothermal stability of the injectable hydrogel obtained in Example 3.
[0029] Fig. 9 The temperature rise curves of the injectable hydrogel at different polydopamine nanoparticle PDA concentrations and the temperature rise curve of the injectable hydrogel obtained in Example 3 at different laser powers.
[0030] Fig.10 Micro-CT images of the alveolar bone around the maxillary first molars of rats in different treatment groups. DETAILED DESCRIPTION
[0031] The present invention is further described below by means of specific implementation methods. The following examples are preferred implementation methods of the present invention, but the implementation methods of the present invention are not limited to the following examples.
[0032] Embodiment 1:
[0033] An injectable hydrogel based on a gradient structure, the preparation method of which comprises the following steps:
[0034] (1) Synthesis of polydopamine nanoparticles (PDA)
[0035] A mixture containing concentrated ammonia (2 mL), ethanol (40 mL) and ultrapure water (90 mL) was stirred at room temperature for 0.5 h. A solution of dopamine hydrochloride (0.5 g) in ultrapure water (10 mL) was added to the mixture, and the reaction was stirred for 1 day. Then, PDANPs were separated by centrifugation at 11000 rpm for 20 min, washed 3 times with ultrapure water, and dried overnight to obtain polydopamine nanoparticles.
[0036] Depend on Figure 1 It can be seen that the polydopamine nanoparticles PDA prepared in step (1) have a uniform particle size of about 200 nm.
[0037] (2) Preparation of drug-loaded polydopamine copper chloride solution
[0038] Take 100 mg of the polydopamine nanoparticles obtained in step (1) and dissolve them in 4 mL of ultrapure water, stir them thoroughly to dissolve, then add 100 mg of genistein and stir them at 600 rpm for 1 day, then add 1 mL of 3.8 wt % copper chloride solution and stir them thoroughly to dissolve to obtain a drug-loaded polydopamine copper chloride solution.
[0039] (3) Preparation of Four-arm-Polyethylene Glycol-Thiol Solution
[0040] Take 1 g of four-arm-polyethylene glycol-thiol and dissolve it in 19 mL of ultrapure water, and fully dissolve it by ultrasonication to obtain a 5 wt % four-arm-polyethylene glycol-thiol solution.
[0041] (4) Preparation of PGCP injectable hydrogel
[0042] Use a dual injector to take the drug-loaded polydopamine copper chloride solution and the four-arm-polyethylene glycol-thiol solution in step (2) and step (3) respectively, and mix them in a volume ratio of 3:1. By mixing them evenly in a syringe, an injectable hydrogel can be obtained.
[0043] Embodiment 2:
[0044] An injectable hydrogel based on a gradient structure, the preparation method of which comprises the following steps:
[0045] (1) Synthesis of polydopamine nanoparticles (PDA)
[0046] A mixture containing concentrated ammonia (2 mL), ethanol (40 mL) and ultrapure water (90 mL) was stirred at room temperature for 0.5 h. A solution of dopamine hydrochloride (0.5 g) in ultrapure water (10 mL) was added to the mixture, and the reaction was stirred for 1 day. Then, PDANPs were separated by centrifugation at 11000 rpm for 20 min, washed 3 times with ultrapure water, and dried overnight to obtain polydopamine nanoparticles.
[0047] (2) Preparation of drug-loaded polydopamine copper chloride solution
[0048] Take 100 mg of the polydopamine nanoparticles obtained in step (1) and dissolve them in 4 mL of ultrapure water, stir them thoroughly to dissolve, then add 100 mg of genistein and stir them at 600 rpm for 1 day, then add 1 mL of 13.8 wt % copper chloride solution and stir them thoroughly to dissolve to obtain a drug-loaded polydopamine copper chloride solution.
[0049] (3) Preparation of Four-arm-Polyethylene Glycol-Thiol Solution
[0050] Take 2 g of four-arm-polyethylene glycol-thiol and dissolve it in 18 mL of ultrapure water, and fully dissolve it by ultrasonication to obtain a 10 wt % four-arm-polyethylene glycol-thiol solution.
[0051] (4) Preparation of PGCP injectable hydrogel
[0052] Use a dual injector to take the drug-loaded polydopamine copper chloride solution and the four-arm-polyethylene glycol-thiol solution in step (2) and step (3) respectively, mix them in a volume ratio of 2:1, and mix them evenly in a syringe to obtain an injectable hydrogel PGCP.
[0053] Embodiment 3:
[0054] An injectable hydrogel, the preparation method of which comprises the following steps:
[0055] (1) Synthesis of polydopamine nanoparticles (PDA)
[0056] Typically, a mixture containing concentrated aqueous ammonia (2 mL), ethanol (40 mL) and ultrapure water (90 mL) was stirred at room temperature for 0.5 h. A solution of dopamine hydrochloride (0.5 g) in ultrapure water (10 mL) was added to the mixture, and the reaction was stirred for 1 day. Then, PDANPs were separated by centrifugation at 11,000 rpm for 20 min, washed 3 times with ultrapure water, and dried overnight to obtain polydopamine nanoparticles.
[0057] (2) Preparation of drug-loaded polydopamine copper chloride solution
[0058] Take 100 mg of the polydopamine nanoparticles obtained in step (1) and dissolve them in 4 mL of ultrapure water, stir them thoroughly to dissolve, then add 100 mg of genistein and stir them at 600 rpm for 1 day, then add 1 mL of 0.8 wt % copper chloride solution and stir them thoroughly to dissolve to obtain a drug-loaded polydopamine copper chloride solution.
[0059] (3) Preparation of Four-arm-Polyethylene Glycol-Thiol Solution
[0060] Take 1 g of four-arm-polyethylene glycol-thiol and dissolve it in 19 mL of ultrapure water, and fully dissolve it by ultrasonication to obtain a 5 wt % four-arm-polyethylene glycol-thiol solution.
[0061] (4) Preparation of PGCP injectable hydrogel
[0062] Use a dual injector to take the drug-loaded polydopamine copper chloride solution and the four-arm-polyethylene glycol-thiol solution in step (2) and step (3) respectively, and mix them in a volume ratio of 1:1. By mixing them evenly in a syringe, an injectable hydrogel PGCP can be obtained.
[0063] Figure 3 The elemental analysis (left) and Raman spectrum analysis (right) of the injectable hydrogel obtained in Example 3 are shown in the spectrometer. The elemental analysis of the spectrometer shows that the N, S and Cu elements are evenly distributed in the network of the injectable hydrogel constructed based on Cu-S and Cu-N coordination bonds; the Raman spectrum analysis shows that the Raman shift of the Cu-S coordination bond of the PCP hydrogel constructed based on Cu-S and Cu-N coordination bonds is 261.7 cm -1 The Raman shift of Cu-N coordination bond is 465.0 cm -1 .
[0064] like Figure 4 As shown, the morphology of the freeze-dried PGCP injectable hydrogel was observed using scanning electron microscopy, and the results showed that it successfully formed a network based on Cu-S and Cu-N coordination bonds, with a structure with a gradient distribution from small pore size to large pore size.
[0065] Figure 5 This is a rheological analysis test diagram of the prepared PGCP injectable hydrogel. G' represents the storage modulus; G" represents the loss modulus. It can be seen that the storage modulus (G') of the PGCP hydrogel is greater than the loss modulus (G"), and it is in a stable gel state for a long time of 10 minutes.
[0066] Figure 6 The injectability of PGCP hydrogel was investigated, and the hydrogel dressing was added into a syringe, and then the letter "Ee" was injected. This showed that the PGCP injectable hydrogel had good injectability.
[0067] Figure 7 The obtained PGCP injectable hydrogel was illuminated by 808 nm laser at 1.1 W / cm 2 Thermal imaging under power density. It can be seen from the figure that it can reach 50℃ within 6 minutes.
[0068] Figure 8 This is the photothermal stability effect diagram of PGCP hydrogel. It can be seen that the PGCP injectable hydrogel reaches the highest temperature within 4 minutes and can also be reduced to the starting temperature within 10 minutes, and maintains a good photothermal stability within 6 cycles.
[0069] To determine the thermal conversion performance of PGCP hydrogel, an 808 nm laser was used at 1.1 W / cm 2 Power irradiation PGCP hydrogel, specific test results see Fig. 9 After 4 minutes of illumination, the temperature can reach 52°C.
[0070] Depend on Fig. 9 (Left) It can be seen that the temperature of the hydrogel rises rapidly in the first 48 seconds of irradiation. As the proportion of the PDA component in the hydrogel system increases, the temperature of the hydrogel rises higher, and it approaches the highest temperature when the proportion of PDA is only 9.8wt‰. Fig. 9 (Right) The temperature rise of the hydrogel shows a certain power dependence. From the application point of view, the power density is 1.1W / cm 2 Compared with the other several, it is more suitable, the heating curve is gentle, and the heating will not be too fast. Therefore, the specific gravity of PDA is preferably 9.8wt‰ and 1.1W / cm 2 The thermal density.
[0071] Comparative Example 1:
[0072] An injectable hydrogel, the preparation method of which comprises the following steps:
[0073] (1) Synthesis of polydopamine nanoparticles (PDA)
[0074] Typically, a mixture containing concentrated aqueous ammonia (2 mL), ethanol (40 mL) and ultrapure water (90 mL) was stirred at room temperature for 0.5 h. A solution of dopamine hydrochloride (0.5 g) in ultrapure water (10 mL) was added to the mixture, and the reaction was stirred for 1 day. Then, PDANPs were separated by centrifugation at 11,000 rpm for 20 min, washed 3 times with ultrapure water, and dried overnight to obtain polydopamine nanoparticles.
[0075] (2) Preparation of polydopamine copper chloride solution
[0076] Take 200 mg of the polydopamine nanoparticles obtained in step (1) and dissolve them in 4 mL of ultrapure water. Stir the mixture at 600 rpm for 1 day to fully dissolve the mixture. Then add 1 mL of 0.8 wt % copper chloride solution and stir the mixture to fully dissolve the mixture to obtain a polydopamine copper chloride solution.
[0077] (3) Preparation of Four-arm-Polyethylene Glycol-Thiol Solution
[0078] Take 1 g of four-arm-polyethylene glycol-thiol and dissolve it in 19 mL of ultrapure water, and fully dissolve it by ultrasonication to obtain a 5 wt % four-arm-polyethylene glycol-thiol solution.
[0079] (4) Preparation of PCP injectable hydrogel
[0080] Use a double injector to take the polydopamine copper chloride solution and the four-arm-polyethylene glycol-thiol solution in step (2) and step (3) respectively, and mix them in a volume ratio of 1:1. By mixing them evenly in a syringe, an injectable hydrogel PCP can be obtained.
[0081] Example 5: Rat Model Studies
[0082] In order to evaluate the effect of the prepared PGCP hydrogel on the alveolar bone of experimental periodontitis rats, the rats were divided into a control group (control), a periodontitis model group (model), a PCP hydrogel group and a PGCP hydrogel group. A periodontitis model was established by ligating the maxillary second molars on both sides of the rats with 4-0 silk thread. The PCP hydrogel group was injected into the gingival sulcus of the rats with 20 μL of the PCP hydrogel prepared in Example 1 once every 3 days, and the 1.1W / cm 2 The near-infrared lamp was irradiated for 4 minutes, and the administration cycle was 15 days. In the PGCP hydrogel group, 20 μL of the PGCP hydrogel prepared in Example 3 was injected into the gingival sulcus of rats once every 3 days, and the 1.1 W / cm2 The near-infrared lamp was irradiated for 4 minutes, and the drug administration period was 15 days. After the rats were killed, Micro-CT scanning was performed on the right alveolar bone specimens of the rats, and three-dimensional reconstruction and cross-sectional analysis of the alveolar bones of the rats in each group were performed.
[0083] The results are as follows Fig.10 As shown in the figure, there was no obvious damage to the alveolar bone around the first molar of rats in the control group (control); while the alveolar bone defect in the periodontitis model group (model) was significant, with exposed roots and obvious root bifurcation, proving that the periodontitis model was successfully constructed. After PCP hydrogel treatment, the alveolar bone in the PCP hydrogel group was effectively regenerated, but there was still a certain gap compared with the control group. In addition, the alveolar bone regeneration effect of the PGCP hydrogel group was significantly better than that of the PCP hydrogel group using only copper ions, indicating that copper ions and genistein have a synergistic effect in the treatment of periodontitis.
Claims
1. A method for preparing an injectable hydrogel based on a gradient structure, characterized in that: The steps include: (1) dissolving polydopamine nanoparticles in a solvent, then adding genistein and stirring to dissolve, then adding a copper chloride solution and stirring to dissolve to obtain a drug-loaded polydopamine copper chloride solution; The mass concentration of the copper chloride solution is 0.16-15wt%; (2) dissolving the four-arm-polyethylene glycol-thiol group in a solvent to obtain a four-arm-polyethylene glycol-thiol group solution; (3) Mixing the drug-loaded polydopamine copper chloride solution with the four-arm-polyethylene glycol-thiol solution to obtain an injectable hydrogel; the mixing volume ratio of the drug-loaded polydopamine copper chloride solution to the four-arm-polyethylene glycol-thiol solution is 1:1-3:
1.
2. The method for preparing an injectable hydrogel based on a gradient structure according to claim 1, characterized in that: In steps (1) and (2), the solvent is ultrapure water, PBS buffer or physiological saline.
3. The method for preparing an injectable hydrogel based on a gradient structure according to claim 1, characterized in that: In step (1), the preparation method of the polydopamine nanoparticles is: stirring a mixture containing concentrated ammonia water, ethanol and water at room temperature; adding an aqueous solution of dopamine hydrochloride to the mixture and reacting under stirring; separating the polydopamine nanoparticles by centrifugation, washing with water, and drying to obtain the polydopamine nanoparticles.
4. The method for preparing the injectable hydrogel based on the gradient structure according to claim 3, characterized in that: The volume ratio of concentrated ammonia water, ethanol and water is 1~3:20~60:45~135, the mass concentration of dopamine hydrochloride added is 25~75 mg / mL, the stirring speed is 400~600 rpm, the stirring temperature is 20~30°C, the centrifugal speed is 10000~12000 r / min, and the centrifugal time is 20~30 min.
5. The method for preparing an injectable hydrogel based on a gradient structure according to claim 1, characterized in that: The mass concentration of the polydopamine nanoparticles in the injectable hydrogel is 4.9-19.6‰.
6. The method for preparing an injectable hydrogel based on a gradient structure according to claim 1, characterized in that: In step (2), the mass concentration of the four-arm-polyethylene glycol-thiol solution is 1-25wt%.
7. An injectable hydrogel based on a gradient structure, prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the injectable hydrogel based on the gradient structure according to claim 7 in the preparation of drugs for treating periodontitis.
Citation Information
Patent Citations
Nano-composite wound repair gel for diabetic ulcer and preparation method of nano-composite wound repair gel
CN116271200A